[tex]f(x) = 2x - 5[/tex]
[tex]f( - 1) = 2 \times ( - 1) - 5 [/tex]
[tex]f( - 1) = - 2 - 5[/tex]
[tex]f( - 1) = - 7[/tex]
[tex]f(0) = 2 \times 0 - 5[/tex]
[tex]f(0) = 0 - 5[/tex]
[tex]f(0) = - 5[/tex]
[tex]f(2) = 2 \times 2 - 5[/tex]
[tex]f(2) = 4 - 5[/tex]
[tex]f(2) = - 1[/tex]
[tex]f( - 2 \sqrt{9} ) = f( - 2 \times 3) = f( - 6)[/tex]
[tex]f( - 6) = 2 \times ( - 6) - 5[/tex]
[tex]f( - 6) = - 12 - 5[/tex]
[tex]f( - 6) = - 17[/tex]
Ordinea crescătoare este :
[tex]f( - 2 \sqrt{9} ),f( - 1),f( 0),f(2).[/tex]